Jurisprudence of Religiosity and Its Social Effects A Contemporary View - Shehab , Muthanna (Islamic Sciences Journal, 2023)
ABSTRACT Religiosity is an innate need for human beings since Allah created Adam, peace be upon him. Human beings vary in the extent of adherence to the religion according to their proximity or distance from their healthy instinct in which they were born, and the extent of their vulnerability to the environment in which they were raised. Because God Almighty instincts all people to believe in Him and to turn to Him as in the case with all other creatures. Allah Almighty said: So make your face up to the religion pure, and Allah has instinctively created the people upon which there is no substitution for Allahs creation that valuable religion but most people do not know. It can be said that the religious person or the observant is compatible with his instinct and followed what he has embarked on. As for the one who neglects the teachings of the religion, he contradicts what he has embarked upon, but that individual can return and his readiness to return to the right path if Allah desires for him to do so, and it the reasons are available to get him back to the correct avenne.